Analisis Pengaruh Kinerja Perusahaan Terhadap Pengungkapan ISR Bank Umum Syariah Tahun 2010-2014 - Nia Fajriyatun Nadlifiyah; Nisful Laila (Jurnal Ekonomi Syariah Teori dan Terapan, 2017)
The Effect of Corporate Performance Toward of ISR Disclosure for Shariah Commercial Bank (BUS) in Indonesia During 2010-2014. This research aims to find out the effect of corporate performance toward of ISR disclosure for Shariah Commercial Bank. Population in this study are all Shariah Commercial Bank in Indonesia During 2010-2014. The total number of sample in this study were seven Shariah Commercial Bank with method is purposive sampling. This research used content analysis method to analysis ISR disclosure bank’s to annual report. This research uses panel data regression analysis technique. The result shows that simultaneously the company size, company age, profitability, and liquidity have significant effect toward of ISR disclosure. Company Age and profitability partially have significant effect toward of ISR disclosure, while company size, and liquidity partially doesn’t have significant effect toward of ISR disclosure.